CHALCONE DERIVATIVES AS NRF2 ACTIVATORS - BISWAL, SHYAM; KUMAR, VINEET; JUNG-HYUN, KIM; THIMMULAPPA, RAJESH; MALHOTRA, SANJAY, V; KUMAR, SARVESH (2012)
Compounds and methods for treating or preventing a disease, disorder or condition associated with an Nrf2-regulated pathway, including those associated with an autoimmune disease, comorbidity associated with diabetes, such as retinopathy and nephropathy, bone marrow transplant for leukemia and related cancers, bone marrow deficiencies, inborn errors of metabolism, and other immune disorders, oxidative stress, respiratory infection, ischemia, neurodegenerative disorders, radiation injury, neutropenia caused by chemotherapy, autoimmunity, and congenital neutropenic disorders, and for restoring a corticosteroid responsiveness, in a subject are provided. La présente invention concerne des composés et des procédés pour traiter ou prévenir une maladie, un trouble ou une affection associé(e) à une voie régulée par Nrf2, comprenant ceux ou celles associé(e)s à une maladie auto-immune, une comorbidité associée au diabète, telle que la rétinopathie et la néphropathie, une transplantation de moelle osseuse pour une leucémie et des cancers associés, des déficiences de moelle osseuse, des maladies enzymatiques, et d'autres troubles immunitaires, le stress oxydatif, une infection respiratoire, une ischémie, des troubles neurodégénératifs, une lésion par rayonnement, une neutropénie causée par une chimiothérapie, l'auto-immunité, et des troubles neutropéniques congénitaux, et pour restaurer une réponse aux corticostéroïdes, chez un sujet.